Review of incisional hernias - Muñoz Delgado, Gustavo E.; Lastra Santiago, Maria A. (International Surgery Journal, 2023)
The 10 to 15% of patients get incisional hernias following any type of abdominal wall incision, with midline wounds carrying a larger risk (3 to 20%). Infection at the surgery site, obesity, smoking, malnutrition, and poor surgical technique are risk factors. Clinical signs include an abdominal bulge at or near a prior incision, which, in non-obese individuals, is frequently identified by palpating the split borders of the fascial defect. CT imaging is particularly useful for complicated ventral hernias, which are characterized by enormous size or considerable loss of dominance. For the purpose of detecting any contents within the hernia sac and deciding whether preoperative abdominal expansion is necessary to lower the risk of postoperative abdominal compartment syndrome, preoperative CT imaging is crucial. When clinically necessary, surgeons should think about making an incision outside the midline and employ the proper fascia closure procedures to lower the likelihood of an incisional hernia. Although the implantation of preventative mesh during the closure of abdominal incisions is being studied, routine usage is not advised owing to probable long-term problems. Incisional hernias can be treated surgically or expectantly, and the patient should be informed of both options.